The Palgrave handbook of the history of women on stage - Sewell, Jan; Smout, Clare (Cham, Switzerland Palgrave Macmillan, 2019)
This book brings together nearly 40 academics and theatre practitioners to chronicle and celebrate the courage, determination and achievements of women on stage across the ages and around the globe. The collection stretches from ancient Greece to present-day Australasia via the United States, Soviet Russia, Europe, India, South Africa and Japan, offering a series of analytical snapshots of women performers, their work and the conditions in which they produced it. Individual chapters provide in-depth consideration of specific moments in time and geography while the volume as a whole and its juxtapositions stimulate consideration of the bigger picture, underlining the challenges women have faced across cultures in establishing themselves as performers and the range of ways in which they gained access to the stage. Organised chronologically, the volume looks not just to the past but the future: it challenges the very notions of 'history', 'stage' and even the definition of 'women' itself.
Includes index.
Keywords: Actresses -- History; Women in the theater -- History